Discourse of Logistics and Transportation - Dževerdanović Pejović, Milena (Promet - Traffic&Transportation, 2020)
The discourse approach for analysing various specified genres and professional discourse communities has increased in recent decades. Globalisation and synergy of disciplines opened up space for the interdisciplinary studies. The analysis of the specialized discourses enables to reveal the peculiarities and dominant concepts of the professional fields. With this in mind, this paper aims to examine the features of discourse employed in the research articles and publications about transport and logistics. The paper analyses the structural and qualitative aspect of the discourse of logistics and transportation. Based on the move/steps model, the main components of the research article in this discourse domain are found. Then, the analysis is focused on the discourse indicators that differ logistics and transportation genres from other academic genres. The changes in the scope and interest domain of logistics are worth“tracking and tracing” from a discursive aspect. The research is carried out on the material compiled of the academic research articles on logistics and transportation, referential resources in the field, and logistic dictionaries. The analysis shows that changes in logistics and transportation correlate with discourse changes. On a diachronic level, many concepts are replaced by new ones containing new approaches and dimensions in logistics. The analysis conducted in this paper brings new insight to both disciplines, logistics and linguistics.